"The Heartbreak of Social Rejection": Young Children's Expressions about How They Experience Rejection from Peers in ECEC. Issue 3 (2nd July 2020) - Nergaard, Kari
ABSTRACT: Playful interactions with peers have a significant role in children's lives, and experiencing belongingness and acceptance through interpersonal relationships is a fundamental presupposition for children's health and well-being. Peer rejections appear to be an inevitable component of peer interactions. Sometimes, rejection involves relational devaluation and deprivation of a sense of belonging. This article highlights the voice of the children and intends to contribute more knowledge about how peer rejections are experienced by the children in early childhood education and care (ECEC) institutions. The data were collected through video-recorded interviews with children between 3.5 and 6 years old and analysed within a phenomenological hermeneutical approach to examine the structures of their experiences. The findings reveal that the peer rejections are experienced as stressful and emotionally painful events, which affect the children's emotional state and impact their social self-perception. This study emphasizes the children as relationally dependent subjects, and the findings highlight the importance of creating within ECECs an inclusive and nurturing social environment that prevents peer rejections.